An assessment of soil loss and natural hazards in Nepal - Shiwakoti, Dinesh R. (Journal of Nepal Geological Society, 2000)
This paper briefly reviews the status of soil erosion in Nepal, and examines the major causes and factors leading to soil erosion and mass movements. There are the following four major mechanisms associated with soil loss: a) surface soil erosion, b) landslide and debris flow, c) earthquake, and d) glacier lake outburst flood. Effective methods for investigating, analysing, identifying, and implementing the critical factors for protecting accelerated soil loss in a planned manner are essential from the grass roots to national and international levels.